They are Just the Same; Everyday Life of Terrorists’ Families in East Java Indonesia - Zakiyah; Koeswinarno; Farida, Anik; Wahab (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2023)
This article aims to investigate the everyday life of terrorists’ families in Surabaya and Sidoarjo East Java Indonesia namely how they have interacted with their neighbors and adapted to the community. Data of this research were gathered through interviews with the neighbors of terrorists’ families and related parties, observing the crime scene of the bombing blast and the neighborhood areas where the terrorist families live, and library research. Results of this study show that the terrorist families of suicide bombings and those raided by Detachment 88 Police Squad were recognized as “ordinary people” by their neighbors and colleagues. Their physical appearances were generally just the same as other Muslims living in their neighborhood; even they participated in several social activities held by the community and interacted with their neighbors openly. This can be recognized as their strategy of adaptation. Thus, they were accepted by the surrounding community, and at the same time, they could still maintain their inner goals as a member of e terrorist group. This paper used the theory of adaptation and Islamic law to examine these aspects, especially how Islam sees jihâd and Inghimâs.